Evaluation of Gastric Emptying Time of a Rice-Based Meal Using Serial Sonography. (28th October 2019) - Cho, Eun-Ah; Kim, Mi Sung; Cha, Yun Byeong; Lee, Mi-Suk; Song, Taejong
Abstract : The aim of this prospective study was to evaluate the gastric emptying time of a rice-based meal by serial ultrasonography of the stomach. After baseline ultrasonographic assessment of ten fasted healthy volunteers, volunteers ingested standardized 420 g, 536 kcal rice-based meal (bibimbap), and serial evaluations were performed every hour until the stomach became empty. At baseline, all the participants had an empty stomach. The average time of complete gastric emptying of the rice-based meal was 5.8 ± 0.8 h (95% confidence interval (CI), 5.0 h to 6.5 h). Since the first postintake cross-sectional area (CSA) measurement, a decrease was observed, and CSA was maintained until postprandial 3–4 h (P > 0.05 ). It declined rapidly 4 h after meal intake (P = 0.031 ), reaching the nadir at approximately 6 h after meal intake. The gastric CSA and hunger score showed a positive correlation (correlation r = 0.616, P < 0 ). The rice-based meal is emptied after 5.8 ± 0.8 h on average in healthy volunteers. Based on our results, 6.5 h (upper limit of CI) of fasting after the ingestion of a rice-based meal would be a safe preoperative fasting time, and this is in accordance with the current guidelines for preoperative fasting.